2011
DOI: 10.32607/20758251-2011-3-4-30-37
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells in Tissue Growth and Repair

Abstract: It has been established in the recent several decades that stem cells play a crucial role in tissue renewal and regeneration. Mesenchymal stem cells (MSCs) are part of the most important population of adult stem cells. These cells have hereby been identified for the very first time and subsequently isolated from bone marrow stroma. Bone marrow-derived MSCs have been believed to play the role of a source of cells for the renewal and repair of connective tissues, including bone, cartilage and adipose tissues. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 63 publications
0
51
0
3
Order By: Relevance
“…In recent years, MSCs have been recognized as one of the adult stem cell types, which actively participate in a tissue damage repair processes 50,51. In a case of tissue damage, the MSCs located in immediate vicinity or originated from bone marrow begin to migrate to the site of injury 28,29.…”
Section: Activities Of Mscs In Damaged Tissue Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, MSCs have been recognized as one of the adult stem cell types, which actively participate in a tissue damage repair processes 50,51. In a case of tissue damage, the MSCs located in immediate vicinity or originated from bone marrow begin to migrate to the site of injury 28,29.…”
Section: Activities Of Mscs In Damaged Tissue Environmentmentioning
confidence: 99%
“…In a case of tissue damage, the MSCs located in immediate vicinity or originated from bone marrow begin to migrate to the site of injury 28,29. Once the MSCs reach an injury site, they must cooperate closely with various types of stromal and inflammatory cells in order to participate in damage repair and regeneration processes 51,56. It has been shown that there are mutual interactions between the MSCs and inflammatory cells, which at the end determine the results of damaged tissue repair processes mediated by MSCs.…”
Section: Activities Of Mscs In Damaged Tissue Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult tissues often harbor resident stem cells or progenitor cells for tissue homeostasis 43 . TGFβs, in consultation with the other signals, appear to regulate stem cells’ decision in differentiation or self-renew.…”
Section: Temporal-spatial Activation Of Extracellular Matrix Latent Tgfβmentioning
confidence: 99%
“…MSCs serve to replenish the differentiated compartment of various cell types for bone formation, angiogenesis, adipogenesis and chondrogenesis 6162, 43, 63–65 . Extrinsic signals in the surrounding microenvironment that are transmitted to the stem cell niche substantially influence MSC self-renewal or differentiation.…”
Section: Dynamic Changes In Bone Microenvironment During Bone Remodelingmentioning
confidence: 99%